The influence of residual loads on the axial load?displacement response of piles in sand - O'Kelly, Brendan (Transportation Research Board, Washington, DC, 2015)
This paper investigates the effects of residual loads developed during installation on the axial load–displacement response of displacement piles at two sites. At the first site, open- and closed-ended piles were installed by jacking into a loose sand deposit. At the second site, an open-ended pile was driven into medium dense sand. The instrumented piles used were of twin-wall construction, allowing separation of the base and shaft loads during pile installation and load testing, thereby facilitating accurate measurements of the residual stresses. For open-ended piles, the development of residual stresses during installation was found to depend on the degree of soil plugging. The pile jacked into the loose sand became fully plugged, resulting in relatively large end-bearing stresses mobilized during installation. Between jacking strokes (when the pile head was unloaded), large residual shear stresses developed at the pile–soil interface on both the external and internal walls of the pile; hence relatively large end-bearing stresses were able to mobilize. Piles that developed large residual stresses exhibited stiffer load–displacement responses when loaded in compression. However, during first-time loading in tension, the piles exhibited relatively soft stiffness responses which were due to the presence of residual stresses
Transportation Research Board 94th Annual Meeting
ACCEPTED
Washington, DC, USA
Keywords: Open-ended pile; Plugging; Residual load; Tension loading; Smart & Sustainable Planet; CPT testing; END-BEARING PILES; GEOTECHNICAL ENGINEERING; Geotechnics; PILES & PILING; Soil Mechanics; Soil Mechanics & Foundations; geotechnical